A study on religious and secular holiday effect: evidence from Malaysian stock market - Loh, Hui San (2013)
This paper investigates the presence of holiday effect in the Malaysian stock market by comparing daily stock returns on the trading day around holiday period with the daily stock returns on normal trading days. To examine the holiday effect more specifically, the public holidays in Malaysia are categorized into religious holiday and secular holiday. The sample of this study comprises daily closing price of FTSE Bursa Malaysia KLCI over a period of eight years from year 2005 to 2012. This paper uses one trading day before and after a holiday to represent the pre- and post-holiday effects. The holiday effects are analysed using descriptive analysis and regression analysis with dummy variable. Results show that the secular holiday effect is stronger than the religious holiday effect in the Malaysian stock market. However, when the impact of global financial crisis is considered, the secular holiday effect in Malaysia disappears during and after the global financial crisis. Only the return during postreligious holiday trading day exhibits significant effect after the crisis. The prereligious holiday effect does not exist in the Malaysian stock market. This study concludes that the Malaysian stock market is not informationally efficient sinceholiday effect is present in the stock market. However, the holiday effect in Malaysia is not persistent and tends to disappear over time. Investors should therefore increase their awareness if they wish to realizeabnormal return from the holiday anomalies in the market